2014
DOI: 10.2298/fuee1404479t
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of hot-carrier degradation based on thorough carrier transport treatment

Abstract: We present and validate a physics-based model for hot-carrier degradation. The model is based on a thorough carrier transport treatment by means of an exact solution of the Boltzmann transport equation. Such important ingredients relevant for hot-carrier degradation as the competing mechanisms of bond dissociation, electron-electron scattering, the activation energy reduction due to the interaction of the dipole moment of the bond with the electric field as well as statistical fluctuations of this energy are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…It should be noted that the mentioned effects on different electron devices have been investigated over the last three decades. [2][3][4][5][6] In earlier studies of CMOS transistor instabilities, it was shown that the effects of irradiation-induced positive gate oxide charges and interface traps on device electrical parameters were very similar to those observed during electrical stress. [7][8][9] Further investigations in this field have indicated that there were some similarities between the mentioned effects in the case of power vertical double-diffused metal oxide semiconductor (VDMOS) transistors as well.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the mentioned effects on different electron devices have been investigated over the last three decades. [2][3][4][5][6] In earlier studies of CMOS transistor instabilities, it was shown that the effects of irradiation-induced positive gate oxide charges and interface traps on device electrical parameters were very similar to those observed during electrical stress. [7][8][9] Further investigations in this field have indicated that there were some similarities between the mentioned effects in the case of power vertical double-diffused metal oxide semiconductor (VDMOS) transistors as well.…”
Section: Introductionmentioning
confidence: 99%